Effect of Dzyaloshinskii–Moriya interaction on Heisenberg antiferromagnetic spin chain in a longitudinal magnetic field - Pham, H. Thao; Ngo, T. Thuan; Le, T. Trang; Hoang, D. Long; Phan, T. H. Ny; Nguyen, H. Canh (Hue University Journal of Science: Natural Science, 2021)
Using functional integral method for the Heisenberg antiferromagnetic spin chain with the added Dzyaloshinskii-Moriya Interaction in the presence of the longitudinal magnetic field, we find out expression for free energy of the spin chain via spin fluctuations, from which quantities characterize the antiferromagnetic order and phase transition such as staggered and total magnetizations derived. From that, we deduce the significant effect of the Dzyaloshinskii-Moriya interaction on the reduction of the antiferromagnetic order and show that the total magnetization can be deviated from the initial one under the influence of canting of the spins due to a combination of the Dzyaloshinskii-Moriya interaction and the magnetic field. Besides, the remarkable role of the transverse spin fluctuations due to the above factors on the antiferromagnetic behaviours of the spin chain is also indicated.